One-tissue compartment model for myocardial perfusion quantification with N-13 ammonia PET provides matching results: A cross-comparison between Carimas, FlowQuant, and PMOD - Nesterov Sergey V.; Sciagrà Roberto; Orozco Luis Eduardo Juarez; Prior John O.; Settimo Leonardo; Han Chunlei; Deshayes Emmanuel; deKemp Robert A.; Ryzhkova Darja V.; Gwet Kilem L.; Knuuti Juhani M. (Springer, 2022)
Purpose
To cross-compare three software packages (SPs)-Carimas, FlowQuant, and PMOD-to quantify myocardial perfusion at global, regional, and segmental levels.
Materials and Methods
Stress N-13 ammonia PET scans of 48 patients with HCM were analyzed in three centers using Carimas, FlowQuant, and PMOD. Values agreed if they had an ICC > 0.75 and a difference < 20% of the median across all observers.
Results
When using 1TCM on the global level, the agreement was good, and the maximum difference between 1TCM MBF values was 17.2% (ICC = 0.83). On the regional level, the agreement was acceptable except in the LCx region (25.5% difference, ICC = 0.74) between FlowQuant and PMOD. Carimas-1TCM agreed well with PMOD-1TCM and FlowQuant-1TCM. Values obtained with FlowQuant-1TCM had a somewhat lesser agreement with PMOD-1TCM, especially at the segmental level.
Conclusions
The global and regional MBF values (with one exception) agree well between the different software packages. There is significant variability in segmental values, mainly located in the LCx region and segments. Out of the studied tools, Carimas can be used interchangeably with both PMOD and FlowQuant for 1TCM implementation on all levels-global, regional, and segmental.